Design and Fabrication of Balancing Gyroscope - Lenin Rakesh, N.; Srinath, R.; Shankar Kannan, P.; Hari Govindhan, R.L. (International Journal of Psychosocial Rehabilitation, 2019)
Whenever a rotating body experiences a force on its axis of rotation, a couple is formed on the rotating body. This couple is known as gyroscopic couple and it nullify the force to a certain extent which is proportional to the mass, speed of rotation and radius of gyration. When the applied force exceeds the moment of inertia of the gyroscope then the disc exhibits precession in a plane perpendicular to the plane of force and plane of rotation. In other words, gyroscopic effect arises whenever the axis of rotating body is caused to change direction In this project our objective is to utilize this gyroscopic effect caused by the change in axis of rotation to balance an apparatus in the basic form of a bicycle or bike. This is done by using weighted disc(s) controlled by gyroscopic sensor by changing its axis of rotation and speed of rotation.